INDUCTION OF POST PARTUM OESTRUS WITH HERBAL UTERINE CLEANSER AND OESTRUS STIMULATORY DRUG COMBINATION IN DEONI COWS - MARKANDEYA, N M; PATIL, A D; BHIKANE, A U (The Indian Journal of Animal Reproduction, 2023)
Present investigation was carried out in post partum anoestrus Deoni cows maintained on an organized farm. Cows after 75 days of calving with good health status were confirmed clinically as anoestrus and were included in the present study. Twelve cows were treated with herbal uterine cleanser @ 100 ml drench per day for three days in treatment group with ten days supplementation of two tablets of haematinic minerals daily. The treatment group animals also received herbal heat inducer powder@ 3 gm per 100 kg body weight for three days. Animals from control group were maintained as per routine schedule without treatment. It was observed that 83.33 per cent cows responded within 5.40 ± 2.49 days of treatment and 66.67 per cent animals conceived with 1.63 services per conception as against nil response in control group. Serum blood biochemicals revealed significant increase in haemoglobin, copper, cobalt and iron levels. However, protein levels showed inconsistent results